Efektvitas Pelaksanaan Perkara Cerai Gugat Menggunakan Sistem E-Court di Pengadilan Agama Mentok Kelas II - Devi Devi; Tinggal Purwanto; Reski Anwar (JYRS: Journal of Youth Research and Studies, 2023)
E-court is a court instrument in the form of service to people who want to litigate online. One of the reasons for the birth of the e-court system was based on the need for services in cases that were easer, cheaper, faster and more efficent. This also includes divorce cases where the number of cases always dominates in every court, including the Mentok Religious Court. This research aims to find out how effective the implementation of contested divorce cases is using the e-court system and the factors that influence its implementation at the class II Mentok Religious Court. This type of research is qualitative research with an empirical juridical approach. Data collection techniques were carred out using intervews, observation and documentation. The data analysis technique is carred out in three steps, namely data reduction for agences related to the implementation of e-court, data display or presentation of research data, so that conclusions are drawn that answer the problems of this research. The results of this research show that the effectiveness of implementing divorce cases using the E-court system at the Mentok Class II Religious Court has generally been carred out in accordance with existing regulations, however if measured based on Soerjono Soekanto's theory the implementation is still less effective, this is because there are still several factors which have not been fulfilled properly include legal means and facilites, public awareness factors and cultural factors.